2019
DOI: 10.1016/j.molcel.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Drp1-Zip1 Interaction Regulates Mitochondrial Quality Surveillance System

Abstract: Mitophagy, a mitochondrial quality control process for eliminating dysfunctional mitochondria, can be induced by a response of dynamin-related protein 1 (Drp1) to a reduction in mitochondrial membrane potential (MMP) and mitochondrial division. However, the coordination between MMP and mitochondrial division for selecting the damaged portion of the mitochondrial network is less understood. Here, we found that MMP is reduced focally at a fission site by the Drp1 recruitment, which is initiated by the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 66 publications
3
83
0
Order By: Relevance
“…Fusion complements the complete alleles of the two damaged mitochondria to maintain mitochondrial function and the demand for cell biological energy, which is also a key step in the fight against cell aging (Sato et al, 2006;Twig and Shirihai, 2011). Studies have found that before mitochondrion fission, Drp1 interacts with mitochondrial zinc transporter ZIP1 and mediates Zn 2+ to enter mitochondrial inter-membrane space through coupling mitochondrial calcium uniporter (MCU), thus regulating MMP (Min et al, 2019). However, most Parkindependent mitochondrial autophagy is related to MMP loss (Burman et al, 2017).…”
Section: Mitochondrial Autophagymentioning
confidence: 99%
“…Fusion complements the complete alleles of the two damaged mitochondria to maintain mitochondrial function and the demand for cell biological energy, which is also a key step in the fight against cell aging (Sato et al, 2006;Twig and Shirihai, 2011). Studies have found that before mitochondrion fission, Drp1 interacts with mitochondrial zinc transporter ZIP1 and mediates Zn 2+ to enter mitochondrial inter-membrane space through coupling mitochondrial calcium uniporter (MCU), thus regulating MMP (Min et al, 2019). However, most Parkindependent mitochondrial autophagy is related to MMP loss (Burman et al, 2017).…”
Section: Mitochondrial Autophagymentioning
confidence: 99%
“…It should also be noted that Drp1 performs many functions in addition to mitochondrial fission. Drp1 can interact with many different proteins localized at different subcellular locations, thereby being involved in many biological processes such as peroxisomal fragmentation, vesicle endocytosis/recycling, MMP changes, and cytoskeletal remodeling 29,62 . Indeed, restoration of Drp1 activity to a normal physiological level in the long-term may be difficult to achieve, meaning that alternative robust and druggable targets for ALS therapy are highly desirable.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the morphological changes in the mitochondria in ALS pathology may hint at additional links between mitochondria and MN function. The morphological dynamics of mitochondria are homeostatically controlled by the balance between continuous fission and fusion, and this is necessary for the maintenance of mitochondrial quality 28,29 . Mitochondrial dynamics are controlled by large GTPase dynamin-related proteins, including Dynamin-related protein 1 (Drp1), Mitofusin1/2 (MFN1/2), and Optic atrophy 1 (Opa1) 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Zn 2+ enters the mitochondrial through the Zip1-MCU complex. Once the mitochondria fail to restore MMP, it will undergo division and mitophagy [43]. Bain believed that accumulation of mitochondrial Zn 2+ induced PINK/parkin-mediated mitophagy for dysfunctional mitochondria suffering hypoxia-reoxygenation conditions [44].…”
Section: Discussionmentioning
confidence: 99%